PENDAMPINGAN WIRAUSAHA PAC ANSOR DAN FATAYAT KECAMATAN KEBUMEN DALAM PENGEMBANGAN PRODUK BISNIS MELALUI PLUT-KUMKM: Entrepreneurship Assistance Of PAC Ansor And Fatayat Kebumen District In Business Product Development Through PLUT-KUMKM - Niken Lestari Niken; Diniyatul Kumala; Lulu Addina Shafa; Muhammad Alif Aristya (Pakis Journal Institute, 2023)
This service aims to foster the spirit of PAC GP Ansor and PAC Fatayat entrepreneurs in developing businesses and providing solutions to obstacles when entrepreneurship by conducting business consultations consultant team from PLUT KUMKM. The method carried out in this activity was by doing a mentoring.Â Assistance and empowerment are part of the Participation Action Research (PAR) method.Â Participation Action Research (PAR) is participatory in the sense that it is a necessary condition under which people play a key role in it and have relevant information about the social system (community) that is under review, and that they participate in the design and implementation of the action plan based on the results of the research. The result of the entrepreneurial assistance of PAC GP Ansor and PAC Fatayat who consulted at PLUT KUMKM is that PLUT KUMKM entrepreneurial consulted regarding business or business constraints run by MSME actors, namely Ansor-Fatayat, Kebumen district. Furthermore, the parties provide statements related to the obstacles that exist in their business, the results of the survey conducted, the obstacles faced by entrepreneurs, namely capital, Human Resources (HR), and marketing. In the next stage, the consultants will give time to entrepreneurs whose businesses do not yet have a NIB to make NIB for free.